Positive Parenting from the Perspective of Luqman Al-Hakim - Rahmatullah, Azam Syukur; Marpuah, Siti (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose–This study aims to exlpore more deeply the positive parenting based on QS Luqman verses 13-19, which discusses parenting by Luqman and is made an exemplary role model of